How to Encourage Social Entrepreneurship Action? Using Web 2.0 Technologies in Higher Education Institutions - García-Morales, Víctor Jesus; Martín-Rojas, Rodrigo; Garde-Sánchez, Raquel (Journal of Business Ethics, 2020)
University students will be our future business leaders, and will have to address social problems caused by business by implementing solutions such as social entrepreneurship ventures. In order to facilitate the learning process that will foster social entrepreneurship, however, a more holistic pedagogy is needed. Based on learning theory, we propose that students' social entrepreneurship actions will depend on their learning about CSR and their absorptive capacity. We propose that instructors and higher education institutions can enhance this absorptive capacity by exploiting Web 2.0 technologies. We tested our proposition with a sample of 425 university students using structural equation modeling and found support for the proposed relationships.
Number: 2
Keywords: Entrepreneuriat; Internet; Libre accès; Soutien; social

Redefining Education in the Digital Economy: The Role of Social Innovation-based Learning in Information Systems Education - Abhari, Kaveh; Koobchehr, Farzan; Huxford, Cyrus; Olivares, Fernando; Kohsuwan, Pocky; Sosa, Luis (Amcis 2020 Proceedings, 2020)
Social responsibility is at the core of modern Information Systems (IS) education due to increased attention by society on the ethics, human factors, and social consequences of emerging technologies. With the acknowledgement that most IS education falls short along these areas, this paper sheds light on the application of Social Learning and Social Innovation-based Learning in socially responsible IS Education. The connectivism principles were used to develop a learning model based on social innovation that was then tested by the example of an upper-division course (Systems Analysis) at a state university. The case study results suggested that the proposed learning model can help students to not only see information systems as social systems but also consider themselves as catalysts for positive change enabled by these systems. The findings also confirmed the positive impact of the proposed intervention on students' social skills. This study contributes to the future of IS education by proposing social innovation-based learning as a practical education paradigm for the digital economy.
WOS:000559924502098
Keywords: Accès gratuit sur inscription; Digital; social; Éducation; États-Unis

Social Entrepreneurship - Sumbly, Sangeeta (Entrepreneurship and Big Data, 2021)
Social entrepreneurship is today an imperative across the world. The scarcity of resources, the needs of the growing population, and the growing burden on the environment have made people realize a need for organizations that can be profitable while bringing positive change in society and the environment. Sustainable, out-of-the-box solutions are required for solving social challenges. The onus of providing these solutions are often taken by aspiring entrepreneurs, who see opportunity in the challenges and are willing to take risks to create innovative and effective solutions for society’s benefit. The chapter elucidates the meaning of social entrepreneurship, the difference between commercial and social entrepreneurship, the models of social enterprises in practice, and the recommended methodology to evaluate social impact. The chapter features international case studies (through secondary research) and cases about social entrepreneurs who have dramatically improved the lives of people while being financially sustainable – an organization like SELCO Solar Lights Private Ltd, ARMAAN, Yellow Leaf and Arvind Eye Hospital, and many others have provided solutions for the economically weaker section of society. Many of these new-age social entrepreneurs use Big Data and artificial intelligence to ensure that their initiatives create greater social change. Some of these initiatives are highlighted in the chapter.
Num Pages: 16
Keywords: Big Data; Entrepreneuriat; Réservé UdeM; Social entrepreneurship; social

Social Entrepreneurship - Sumbly, Sangeeta (Entrepreneurship and Big Data, 2021)
Social entrepreneurship is today an imperative across the world. The scarcity of resources, the needs of the growing population, and the growing burden on the environment have made people realize a need for organizations that can be profitable while bringing positive change in society and the environment. Sustainable, out-of-the-box solutions are required for solving social challenges. The onus of providing these solutions are often taken by aspiring entrepreneurs, who see opportunity in the challenges and are willing to take risks to create innovative and effective solutions for society’s benefit. The chapter elucidates the meaning of social entrepreneurship, the difference between commercial and social entrepreneurship, the models of social enterprises in practice, and the recommended methodology to evaluate social impact. The chapter features international case studies (through secondary research) and cases about social entrepreneurs who have dramatically improved the lives of people while being financially sustainable – an organization like SELCO Solar Lights Private Ltd, ARMAAN, Yellow Leaf and Arvind Eye Hospital, and many others have provided solutions for the economically weaker section of society. Many of these new-age social entrepreneurs use Big Data and artificial intelligence to ensure that their initiatives create greater social change. Some of these initiatives are highlighted in the chapter.
Num Pages: 16
Keywords: Big Data; Entrepreneuriat; Réservé UdeM; Social entrepreneurship; social

How to Encourage Social Entrepreneurship Action? Using Web 2.0 Technologies in Higher Education Institutions - García-Morales, Víctor Jesus; Martín-Rojas, Rodrigo; Garde-Sánchez, Raquel (Journal of Business Ethics, 2020)
University students will be our future business leaders, and will have to address social problems caused by business by implementing solutions such as social entrepreneurship ventures. In order to facilitate the learning process that will foster social entrepreneurship, however, a more holistic pedagogy is needed. Based on learning theory, we propose that students' social entrepreneurship actions will depend on their learning about CSR and their absorptive capacity. We propose that instructors and higher education institutions can enhance this absorptive capacity by exploiting Web 2.0 technologies. We tested our proposition with a sample of 425 university students using structural equation modeling and found support for the proposed relationships.
Keywords: Entrepreneuriat; Internet; Libre accès; Soutien; social

Redefining Education in the Digital Economy: The Role of Social Innovation-based Learning in Information Systems Education - Abhari, Kaveh; Koobchehr, Farzan; Huxford, Cyrus; Olivares, Fernando; Kohsuwan, Pocky; Sosa, Luis (Amcis 2020 Proceedings, 2020)
Social responsibility is at the core of modern Information Systems (IS) education due to increased attention by society on the ethics, human factors, and social consequences of emerging technologies. With the acknowledgement that most IS education falls short along these areas, this paper sheds light on the application of Social Learning and Social Innovation-based Learning in socially responsible IS Education. The connectivism principles were used to develop a learning model based on social innovation that was then tested by the example of an upper-division course (Systems Analysis) at a state university. The case study results suggested that the proposed learning model can help students to not only see information systems as social systems but also consider themselves as catalysts for positive change enabled by these systems. The findings also confirmed the positive impact of the proposed intervention on students' social skills. This study contributes to the future of IS education by proposing social innovation-based learning as a practical education paradigm for the digital economy.
WOS:000559924502098
Keywords: Accès gratuit sur inscription; Digital; social; Éducation; États-Unis